Analysis of Key Aroma Presenting Substances in Yak Milk Lala from Different Regions of Tibet Based on HS-SPME-GC-MS and OAV - Chuang DONG; Hui XU; Yahui ZHU; Lin YANG (Shipin gongye ke-ji)
The yak milk Lala (YMLL) from four regions of Tibet were used as the research object, and the headspace-solid phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS) and odor activity value (OAV) were used to identify the key aromatic substances. Additionally, partial least squares discriminant analysis (OPLS-DA) was utilized to explore the key aroma and different components of Lala at different regions, which aimed to analyze the key aroma substances of YMLL in Tibet. The results revealed that 88 volatile components were detected in YMLL at the four regions, which were primarily acids, alcohols, aldehydes, esters, ketones and aromatic compounds. Twenty-nine volatile components with OAV≥1 by threshold value were screened. Furthermore, through a combination of OAV≥1 and impact analysis of projection variables (VIP)>1, 9 characteristic volatile substances as the difference markers of YMLL flavor in the four regions were further identified, that included 2R,3R-butanediol, nonone, butanediol, isovaleric acid, n-methyl-2-pyrrolidine, acetic acid, isobutyric acid, maltol and myristic acid, respectively. The OAV, cluster heat map and OPLS-DA was used to indicate differences in key aroma components of YMLL at different altitudes. The characteristic flavors of Lala in four regions were well distinguished according to these 9 characteristic volatile substances selected by VIP, 2R,3R-butanediol, nonone, butanediol, n-methyl-2-pyrrole formaldehyde and acetic acid gave DXLL sweet taste with grassy notes along with roasted nuts and light sweet-and-sour taste respectively. Isovaleric acid, acetic acid, maltol and myristic acid gave DLLL special sour taste, burnt cream and coco nut aroma respectively. Isovaleric acid and isobutyric acid gave BGLL sour taste. The key aroma composition of YMLL was unveiled in this study, while data support was provided for the elucidation of its characteristic aroma formation, theoretical guidance was additionally offered for the industrial-scale production of YMLL through systematic biochemical characterization.